Numerical modelling of microwave plasma-assisted chemical vapour deposition reactors for diamond synthesis - Marsh, Jonathan (2020)
This thesis studies the numerical modelling of microwave plasma-assisted chemical vapour deposition (MPA-CVD) reactors for synthetic diamond synthesis. Specifically we model the formation of a plasma within these reactors, which is responsible for enabling the deposition of carbon onto a substrate for diamond growth. This involves first introducing a chemically reacting binary gas flow model for a hydrogen gas mixture, which in turn is coupled to an applied electric field operating at resonance. This electric field acts as the energy source for the ionising collisions that characterise plasma formation.